Stepping into a Family Math Night: Reflections on Vulnerability - Vautour, Lindsay; Gerbrandt, Julianne (Antistasis, 2024)
There is something unique about the vulnerability we experience as teachers, and it may be that no subject surfaces vulnerability quite like mathematics. This paper is a reflection on our experiences at a Family Math Night (FMN) as a preservice teacher and as a university instructor, where each of us witnessed and confronted expressions of vulnerability from parents, children, and from each other. In February 2023, the chair of a local area elementary school’s Parent School Support Committee (PSSC) reached out to Julianne about assisting with a FMN. The school was trying to improve students’ fluency with basic computations, also known as ‘math facts’, and they were looking for community support to help with the event. After agreeing, Julianne decided to extend the invitation to Bachelor of Education students who took the elementary mathematics methods course with her in the fall. Two students expressed interest and joined the table, one of whom is the first author of this paper. We will begin by sharing a brief overview of FMNs before sharing how we turned this invitation into a small research project. Following an overview of our methods, we highlight the three themes that emerged from the data: feeling like a fraud, getting it right, and entering ‘the sphere’. We conclude by sharing our lessons learned, our lingering questions, and the implications of our analysis.